RESPONSE OF SOME FORAGE PEA GENOTYPES TO SALT STRESS DURING THE SEEDLING STAGE - Ileri, Onur; Canbay, Abdulsamed; Baran, Mahmut; Koc, Ali (LIFE: International Journal of Health and Life-Sciences, 2017)
Salinity stress is a common problem under dry climatic condition all over the world. The determination of salt tolerant genotypes has a crucial importance to alleviate this problem. Pea known as the most salt tolerant plant among legumes and seedling stage is the most sensitive to salt stress than the other growth stages. The experiment was carried out in the growth chamber to observe tolerance of the examined genotypes to different salt doses. Therefore germination rates, mean germination time (mgt), root/shoot lengths and fresh/dry seedling weights of some forage pea genotypes (Local population, Crackerjack, Golyazi, Ozkaynak, Rose, Taskent, Tore, Ulubatlı) under different salt concentrations (Control, 5, 10, 15 and 20 dS m-1) were determined. The results showed that salinity x genotype interaction was significant among genotypes with respect to all investigated parameters. Crackerjack had the highest germination rate and root length with the increasing salt levels and it was followed by Ozkaynak, Rose, Taskent and Tore. Ozkaynak was the fastest germinated genotype with respect to mgt with 1,92 days and the genotype had the longest shoot length. Fresh seedling weight of Crackerjack was the higher than all other genotypes but there was not a significant difference between Rose and Crackerjack. Results indicated that Taskent, Tore, Ozkaynak, cultivars could be recommended upto moderate saline areas while Crackerjack and Rose could be recommended for slightly saline areas